Relationships among ergot alkaloids, cytochrome P450 activity, and beef steer growth - Rosenkrans, Charles F.; Ezell, Nicholas S. (Frontiers in Chemistry, 2015)
Determining a grazing animal’s susceptibility to ergot alkaloids has been a research topic for decades. Our objective was to determine if the Promega™ P450-Glo assay could be used to indirectly detect ergot alkaloids or their metabolites in urine of steers. The first experiment validated the effects of ergot alkaloids [0, 20, and 40 μM of ergotamine (ET), dihydroergotamine (DHET), and ergonovine (EN)] on human CYP3A4 using the P450-Glo assay (Promega™ V9800). With this assay, luminescence is directly proportional to CYP450 activity. Relative inhibition of in vitro cytochrome P450 activity was affected (P < 0.001) by an interaction between alkaloids and concentration. That interaction resulted in no concentration effect of EN, but within ET and DHET 20 and 40 µM concentrations inhibited CYP450 activity when compared with controls. In experiment 2, urine was collected from Angus-sired crossbred steers (n = 39; 216 ± 2.6 d of age; 203 ± 1.7 kg) after grazing tall fescue pastures for 105 d. Non-diluted urine was added to the Promega™ P450-Glo assay, and observed inhibition (3.7 % ± 2.7 of control). Urine content of total ergot alkaloids (331.1 ng/mg of creatinine ± 325.7) was determined using enzyme linked immunosorbent assay. Urine inhibition of CYP450 activity and total alkaloids were correlated (r = -0.31; P < 0.05). Steers were genotyped at CYP450 single nucleotide polymorphism, C994G. Steer genotype affected (P < 0.03) inhibition of CYP450 activity by urine; heterozygous steers had the least amount of CYP450 inhibition suggesting that genotyping cattle may be a method of identifying animals that are susceptible to ergot alkaloids. Although, additional research is needed, we demonstrate that the Promega™ P450-Glo assay is sensitive to ergot alkaloids and urine from steers grazing tall fescue. With some refinement the P450-Glo assay has potential as a tool for screening cattle for their exposure to fescue toxins.